Análise da legislação ambiental aplicável ao Pantanal pelo Brasil e Bolívia - Fernando Lara Rocha de Almeida (2021)
The Pantanal is the largest wetland complex in the world, has unique characteristics and internationally recognized environmental wealth. It is located in the central part of the South American continent, covering parts of Brazil, Paraguay and Bolivia. Environmental resources are characterized by not complying with physical and political barriers established by man. Thus, there is little point in acting locally in the prevention and repression of pollution, as the consequences are transboundary. Considering that 95% of its area is in Brazil and Bolivia, this work analyzed, through bibliographical research and deductive, historical and comparative methods, the main rules applicable to the Pantanal in these countries, demonstrating its legal status. Studies that analyze and compare the environmental laws of different countries are important tools that can provide the necessary theoretical basis to propose public policies in order to integrate actions, legal orders, preserve the environment and introduce and improve the norms that regulate the relationship human- nature. It was found that there is no shared environmental management agreement or specific standard regulating its use and preservation in both countries. In Brazil, despite the Federal Constitution declaring it as a national heritage, the Pantanal has specific treatments, in some laws, and generic, in its majority. In Bolivia, the Pantanal has recently been recognized as an ecoregion, being protected by general norms. On the other hand, it was observed that 46,720 km2 of the Pantanal are protected areas in Brazil and Bolivia and that the two countries have constitutional and infra-constitutional provisions showing interest in promoting shared/integrated environmental management of natural resources bordering neighboring countries.